Analysis of force and deformation parameters in corrugated clad rolling. (1st April 2023) - Hao, Pingju; Liu, Yuanming; Wang, Zhenhua; Wang, Tao; He, Dongping; Huang, Qingxue; Wang, Zhenguo
Research highlights: The dynamic change states of deformation zone during corrugated rolling are comprehensively analyzed. A new analytical model of force and deformation parameters for corrugated clad rolling is proposed and validated. The distribution laws of vertical and horizontal pressures in deformation zone are found. The variation mechanism of dynamic force and shape parameters in complex corrugated rolling process is revealed. Abstract: Corrugated clad rolling is an emerging and promising technology to produce composite plates with a three-dimensional corrugated interface and excellent performance. A new analytical model is proposed to predict and analyze force and deformation parameters in corrugated clad rolling using the slab method, which solves the problem that there is no suitable analytical model to improve the precision of automatic production control. The analytical model is proposed by selecting a differential element perpendicular to the rolling direction, analyzing the corresponding differential equilibrium equations and calculating the integral constants according to the yield and boundary conditions. Dynamic rolling forces under different contact states between the composite plate and rolls are presented creatively considering the special features of the new corrugated clad rolling that there are multiple complex shapes and stress states in the deformation zone and that there are various outlet conditions of the corrugated composite plate. The accuracy of the proposed analytical model is verified by the comparisons of the calculated values from the model, the FEM results, and the experimental measurements. The error of the proposed model is within 7.36%. The specific rolling pressure distributions along the projected contact arc, the specific horizontal stress distributions along the projected contact arc, the dynamic rolling forces, and the positions of the lower neutral point can be conveniently and accurately calculated by the proposed model, which can help to analyze the mechanism of the corrugated rolling with the variation of the rolling reduction rate, the shear yield stress ratio and the friction factor ratio. The proposed analytical model of dynamic rolling force and deformation parameters is especially suitable for the analysis of the new corrugated clad rolling and can provide technical support for the control precision of automatic production. Graphical abstract: Image, graphical abstract